1996
DOI: 10.1074/jbc.271.28.16586
|View full text |Cite
|
Sign up to set email alerts
|

Big Mitogen-activated Protein Kinase 1 (BMK1) Is a Redox-sensitive Kinase

Abstract: Mitogen-activated protein (MAP) kinases are a multigene family activated by many extracellular stimuli. There are three groups of MAP kinases based on their dual phosphorylation motifs, TEY, TPY, and TGY, which are termed extracellular signal-regulated protein kinases (ERK1/2), c-Jun N-terminal kinases, and p38, respectively. A new MAP kinase family member termed Big MAP kinase 1 (BMK1) or ERK5 was recently cloned. BMK1 has a TEY sequence similar to ERK1/2 but has unique COOH-terminal and loop-12 domains. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
312
2
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(327 citation statements)
references
References 33 publications
12
312
2
1
Order By: Relevance
“…For western blot analysis of Bcr-Abl and Bcr, total proteins were isolated as described (Abe et al, 1996). Blots were probed with either anti-HA (Invitrogen, Carlsbad, CA, USA), antiBcr (1-16) or anti-Abl 8E9 monoclonal antibody (Guo et al, 1994).…”
Section: Protein Analysismentioning
confidence: 99%
“…For western blot analysis of Bcr-Abl and Bcr, total proteins were isolated as described (Abe et al, 1996). Blots were probed with either anti-HA (Invitrogen, Carlsbad, CA, USA), antiBcr (1-16) or anti-Abl 8E9 monoclonal antibody (Guo et al, 1994).…”
Section: Protein Analysismentioning
confidence: 99%
“…It has been recently observed that the osmotic-and oxidative-stress can activate ERK5 (Abe et al, 1996). Analysis of the signaling mechanism indicates that MKK5-ERK5 activation results in the phosphorylation of MEF2C, the transcription factors belonging to the myocyte enhancer factor-2 (MEF2)-family (Kato et al, 1997).…”
Section: Map Kinase Kinase-5mentioning
confidence: 99%
“…Four groups of MAPKs have been identi®ed in mammalian cells; the extracellular signalregulated kinases (ERKs) (also referred to as p42/44 MAPK) (for review see Davis, 1993), the c-Jun Nterminal kinases/stress-activated protein kinases (JNK/ SAPKs) (De rijard et al, 1994;Kallunki et al, 1994;Kyriakis et al, 1994), p38/CSBP/RK/MPK2/MX12 (Han et al, 1994;Lee et al, 1995), and ERK5 (Lee et al, 1997., Abe et al, 1996. The mammalian ERKs are involved in growth factor-mediated activation and di erentiation of a variety of cells, and are activated by growth factors and mitogens such as epidermal growth factor (EGF), PDGF and insulin.…”
Section: Introductionmentioning
confidence: 99%